ANALISIS KESELARASAN RENCANA TATA RUANG DAN PERSEPSI STAKEHOLDER TERHADAP RENCANA REKONSTRUKSI KAWASAN PESISIR DI KOTA PALU - Muntaza, Ibnul; Hidayati, Isti (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The Bay of Palu, a central hub for community activities, including tourism, suffered damages and a decline in activities following the 2018 disaster. As of September 2023, the progress of new development is below 10%, and the sluggish reconstruction is influenced by differing stakeholder perceptions. Identifying four stakeholder groups, including local government, the community, traders, and tourists, is the focal point of this research. The aim is to assess the alignment of stakeholder perceptions with spatial allocation guidelines in the reconstruction plan. Using an interpretative paradigm, this study integrates qualitative and quantitative methods through a questionnaire administered to 171 respondents in Palu City. The results indicate a dominance of stakeholder preferences in development expectations, emphasizing the preservation of spatial functions with improved aesthetics. Additionally, the research identifies alignment between stakeholder expectations and spatial allocation guidelines, emphasizing conservation, tourism, and sustainable development.